Delik Pidana Akses Ilegal (Hacking) terhadap Komputer atau Sistem Elektronik - Inggou David Purba (Bulletin of Community Engagement, 2024)
The aim of this research is to show the correct formulation of offenses in the laws related to cracking down on illegal access to computers or electronic systems, and how to analyze judicially the elements of criminal acts, including the legal consequences. As well as disclosing any criminal offenses that could potentially occur due to illegal access to computers or electronic systems. This research uses a normative juridical approach. The data needed in this research was collected in two types of data; Primary Data is data obtained from the results of a literature review through searching Legislative Regulations, book literature, articles/journals, online news, agency archives, etc., and Secondary Data is data obtained from searching the history of illegal access crimes that are often occurring. Data analysis by processing primary data and secondary data using Descriptive Juridical analysis techniques by analyzing the elements or elements of criminal acts that occur using a criminal theory perspective. The research results reveal that the criminal offense of illegal access (hacking) is formulated in Article 332 of Law no. 1 of 2023 concerning the Criminal Code, by analyzing its objective and subjective elements. Potential criminal offenses that can occur following illegal access (hacking) to computers or electronic systems can be in the form of Online Fraud or the Crime of Cheating, Theft of Personal Data, and Defamation or Insult. The legal consequence of this criminal act is punishment which can result in imprisonment or a fine for the perpetrator.